Breath acetone change during aerobic exercise is moderated by cardiorespiratory fitness - Königstein, Karsten; Abegg, Sebastian; Schorn, Andrea N; Weber, Ines C; Derron, Nina; Krebs, Andreas; Gerber, Philipp A; Schmidt-Trucksäss, Arno; Güntner, Andreas T (Journal of breath research, 2021)
Exhaled breath acetone (BrAce) was investigated during and after submaximal aerobic exercise as a volatile biomarker for metabolic responsiveness in high and lower-fit individuals in a prospective cohort pilot-study. Twenty healthy adults (19-39 years) with different levels of cardiorespiratory fitness (VO2peak), determined by spiroergometry, were recruited. BrAce was repeatedly measured by proton-transfer-reaction time-of-flight mass spectrometry (PTR-TOF-MS) during 40-55 min submaximal cycling exercise and a post-exercise period of 180 min. Activity of ketone and fat metabolism during and after exercise were assessed by indirect calorimetric calculation of fat oxidation rate and by measurement of venous β-hydroxybutyrate (βHB). Maximum BrAce ratios were significantly higher during exercise in the high-fit individuals compared to the lower-fit group (t-test; p= 0.03). Multivariate regression showed 0.4% (95%-CI = −0.2%-0.9%, p= 0.155) higher BrAce change during exercise for every ml kg−1 min−1 higher VO2peak. Differences of BrAce ratios during exercise were similar to fat oxidation rate changes, but without association to respiratory minute volume. Furthermore, the high-fit group showed higher maximum BrAce increase rates (46% h−1) in the late post-exercise phase compared to the lower-fit group (29% h−1). As a result, high-fit young, healthy individuals have a higher increase in BrAce concentrations related to submaximal exercise than lower-fit subjects, indicating a stronger exercise-related activation of fat metabolism.